Spectral homotopy analysis method for solving nonlinear Volterra integro differential equations - Atabakan, Zohreh Pashazadeh; Nasab, Aliasghar Kazemi; Kilicman, Adem (Institute for Mathematical Research, Universiti Putra Malaysia, 2014)
In this paper we proposed Spectral Homotopy analysis method to solve nonlinear Volterra integro-differential equations. Some examples are given to approve the efficiency and the accuracy of the proposed method. The SHAM results show that the proposed approach is quite reasonable when compared to homotopy analysis method and exact analytical solutions.